Improving the Understanding of Students' Learning Concepts on Optical Equipment Materials through Interactive Learning Media - Yanti, Siti Hikma; Yennita, Yennita; Syahril, Syahril (FKIP - Universitas Riau, 2022)
This research was motivated by the lack of learning media that facilitates understanding of students' concepts on optical material. The existing learning media generally integrate the visualization of image formation on mirrors and lenses. Not yet equipped with practice questions and evaluation questions in accordance with the concept understanding indicators. Then the percentage of student learning outcomes that are below the KKM and student learning motivation is low. The purpose of this study is to improve the understanding of students' concepts by using Lectora learning media. The design used in this study was a randomized control group pretest-posttest and the research subjects were students of class XI SMA N 5 Tapung. The control class applied conventional learning and the experimental class applied the use of learning media. The application of Lectora Inspire interactive learning media affects students' conceptual understanding in the experimental class with an average increase of 0.58, and the control class with an average increase of 0.54. The results showed that there were significant differences in conceptual understanding between the experimental group and the control group.